2013
DOI: 10.1002/ardp.201300161
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Biological Activities of New Hybrid Molecules Containing Different Heterocyclic Moieties

Abstract: 4-Aryl-5-(pyridin-3-yl)-4H-1,2,4-triazole-3-(thi)oles 5-7, obtained starting from nicotinic acid hydrazide were converted to the corresponding Mannich bases 12-24 by the reaction with several heterocyclic amines in the presence of formaldehyde. The synthesis of S-alkylated compounds 8-11 was performed from the reaction of the corresponding triazol-5-thioles with various alkyl halides. The condensation of carbo(thio)amides 2-4 with 4-chlorophenacyl bromide afforded the corresponding 1,3-thia(oxa)zol-2(3H)-ylide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…In addition, in one of our previous studies the discovery of some azole compounds as antiurease agents served to merge the azole groups, namely 1,3‐oxazol(idin)e and 1,3‐thiazol(idin)e, with the penicillanic acid skeleton. Another reason for choosing these azole groups for hybridization is that some hybrid compounds carrying 1,3‐oxazol(idin)e or 1,3‐thiazol(idin)e nucleus were obtained as antilipase agents in our laboratory .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in one of our previous studies the discovery of some azole compounds as antiurease agents served to merge the azole groups, namely 1,3‐oxazol(idin)e and 1,3‐thiazol(idin)e, with the penicillanic acid skeleton. Another reason for choosing these azole groups for hybridization is that some hybrid compounds carrying 1,3‐oxazol(idin)e or 1,3‐thiazol(idin)e nucleus were obtained as antilipase agents in our laboratory .…”
Section: Resultsmentioning
confidence: 99%
“…However, further elaboration of 133i into compound 133p abolished the antibacterial activity [174]. Mannich bases 133j, which feature a 3pyridinyl moiety at position 5 of the triazole ring, were generally poorer antibacterials than reference drug ampicillin, although there were isolated examples amongst these candidates that show more potency than ampicillin against certain bacteria [175]. Furthermore, the replacement of 4-pyridinyl with 2-quinolinyl as substituent at position 5 of the triazole ring, and modification of phenyl into benzyl as substituent at position 4 of the triazole ring led to inactive Mannich bases 133k [176].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…25) of 1,2,4-triazole-3-ones having a 2-quinolinyl moiety as substituent at position 5 of the triazole ring was synthesized and evaluated for antibacterial activity, and its effect on E. coli and P. aeruginosa was comparable to that of ampicillin [176]. Three Mannich bases having a 3-pyridinyl moiety at position 5 of 1,2,4-triazole-3-one scaffold, analogous to compounds 133j derived from 1,2,4-triazole-3-thione, had moderate to good activity against most bacteria in the panel, but were not superior to reference drug ampicillin [175].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Therefore it is often introduced 23 into some parent structures to enhance the biological properties 24 during the drug design. It has been found that N-substituted 25 piperazine compounds have a wide range of biological activities, 26 such as antimicrobial [8], anticancer [9], herbicidal and insecticidal 27 activities [10], especially they were often used as antimicrobial 28 agent. Mannich bases of 1,2,4-triazole derivatives containing 29 N-substituted piperazine moiety have been reported to possess 30 antifungal activity [11,12], and some piperazine-containing 4,5-31 disubstituted-1,2,4-triazole Mannich bases were found to have 32 tuberculostatic activity [13].…”
mentioning
confidence: 99%
“…When arylamide-containing 1,2,4-triazole 156 thiol 3 was used, the Mannich reaction also can occur smoothly to 157 give corresponding thione derivatives 4 and 5. Comparing with the 158 usual cases that the (substituted)benzylideneamino or aryl at 4-159 position of 1,2,4-triazole [16,17,25,26], such novel arylamide case 160 expands the application range for the heterocyclic Mannich 161 reaction. It is known that the intermediates 1 and 3 can exist 162 either as a thiol or the thione tautomeric forms or as an equilibrium 163 mixture of both forms owing to the thioamide structure (-NH-164 C(5 5S)).…”
mentioning
confidence: 99%